(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study discussed the benefits of digitization of National Commission for Colleges of Education in Nigeria. The study revealed that improvement in the operation, support effective accreditation progranmme aid effective decision making, effective data management, data security and reduction in operation cost are the benefits of digitization of National Commission for Colleges of Education in Nigeria. Based on the findings, the study suggests the following: increment in the budgetary allocation for the implementation of digitization of National Commission for Colleges of Education project. Government should provide necessary support to the commission to ensure the realization of the project of digitization of National Commission for Colleges of Education by setting up committee to supervise the commission for the programme. Private institutions, religious institutions and international organizations should support the commission with supply of digital infrastructure facilities and capacity building programme for staff of the commission.